Pengaruh Kekuatan Otot Lengan Terhadap Kemampuan Lemparan Ke Dalam (Throw-In) Dalam Permainan Sepak Bola Pada Tim SepakBola SMA Negeri 5 Tidore Kepulauan - Triana Nuryastuti; Yusuf Siolon (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine whether there is an influence of arm muscle strength on the ability to throw-in (throw-in) in soccer games on the SMA Negeri 5 Tidore Islands football team. This research was conducted at SMA Negeri 5 Tidore Kepulauan in 2020. However, the phenomenon that occurs in the field in relation to the ability of players to throw in shows that there are still players whose throwing abilities do not have good strength, where the throws still float a lot without arm muscle strength. Throw-in is a basic football technique that gives a lot of opportunities or creates opportunities to score goals. However, the soccer game on the Tidore Islands 5 State High School soccer team has not shown an effective throw-in technique, sometimes the wrong throw-in is done, and the distance of the throw is not too far. In this study, sample data was collected in the form of experimental research using survey methods. The results of this study show that there is an influence between the strength of the arm muscles on the ability to throw in. Based on the results of the analysis and calculation of the correlation coefficient between arm muscle strength and the ability to throw in, there is a tcount of 10.21 greater than ttable 2.539. arm muscle strength